Recent advances in copper-catalyzed C–H bond amidation - Jie-Ping Wan; Yanfeng Jing (Beilstein Journal of Organic Chemistry, 2015)
Copper catalysis has been known as a powerful tool for its ubiquitous application in organic synthesis. One of the fundamental utilities of copper catalysis is in the C–N bond formation by using carbon sources and nitrogen functional groups such as amides. In this review, the recent progress in the amidation reactions employing copper-catalyzed C–H amidation is summarized.